How to achieve digital well-being in universities. Tackling teachers’ technostress through mentoring Digital - GALGENMÜLLER, Christian; DAVID, Laura Teodora; CAZAN, Ana-Maria (2024)
Technologies have become part of our daily lives in such a manner that it is difficult to consider living without them. Rapidly evolving technologies create many surprising changes to our private and work lives. Novel words such as wireless, browsing, downloading, and uploading, blogging, networking, cyberspace, hyperlink, VR, or old ones that expanded their meaning such as cloud, cookie, file, firewall entered our vocabulary and are now considered to be common knowledge. We are talking about generations like Gen Z or digital native to refer to those born after the year 2000 and who have witnessed technology advance faster than ever. Efforts are being made to understand the consequences of such development and to anticipate appropriate paths to support progress.